2005
DOI: 10.1159/000086112
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sclerectomy versus Punch Trabeculectomy: Effect of Low-Dosage Mitomycin C

Abstract: Purpose: To compare IOP behavior after deep sclerectomy (DS) and trabeculectomy with the Crozafon-De Laage Punch (TP), using low-dosage intraoperative mitomycin C (MMC) in both techniques. Methods: The study was a prospective randomized clinical trial. All patients met inclusion and exclusion criteria, and were scheduled for glaucoma surgery. Forty patients were randomized to undergo either a nonpenetrating DS with MMC (DSMMC) (19 eyes) or a TP with MMC (TPMMC) (21 eyes). Postoperative examinations were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2
34

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 35 publications
4
30
2
34
Order By: Relevance
“…The low complication rate with low-dosage MMC in our sample is in agreement with our previous studies. 8,24,35,36 A recent pilot study 20 is not in agreement with our results, since it showed OLO to have a larger amount of complications than simple trabeculectomy. The conjunctival closure with two simple 10-0 nylon sutures at the flap extremities was probably responsible for a higher incidence of positive Seidel test with flat anterior chamber in the study group, and could have reduced the beneficial effect of the implant in bleb development.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The low complication rate with low-dosage MMC in our sample is in agreement with our previous studies. 8,24,35,36 A recent pilot study 20 is not in agreement with our results, since it showed OLO to have a larger amount of complications than simple trabeculectomy. The conjunctival closure with two simple 10-0 nylon sutures at the flap extremities was probably responsible for a higher incidence of positive Seidel test with flat anterior chamber in the study group, and could have reduced the beneficial effect of the implant in bleb development.…”
Section: Discussioncontrasting
confidence: 75%
“…22,23 When MMC was the randomized adjunctive therapy (Kyowa S.r.l., Milan, Italy), a Weck-cell sponge was cut into two to three pieces, B4 mm  2 mm  0.5 mm, soaked with MMC at a concentration of 0.2 mg/ml and placed under the dissected conjunctiva surrounding the scleral flap 22,23 and on the scleral bed. 24 The sponges were left in position for 2 min in order to maintain contact with the Tenon's capsule side of conjunctiva. Thereafter, the eye was irrigated with 15 ml of balanced salt solution.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Evidence-based data indicate that the use of mytomicin-C (MMC) during trabeculectomy has a significant positive effect on postoperative intraocular pressure (IOP) (Jampel et al 2002;Wilkins et al 2005). In our experience, MMC can be regarded as an enhancement of the deep sclerectomy IOP-lowering effect without evidence of antimetabolite-related complications (Cillino et al 2005). On the other hand, MMC-augmented glaucoma surgery can be associated with a significantly higher frequency of late bleb leaks (Anand & Atherley 2005;Anand et al 2006).…”
Section: Introductionmentioning
confidence: 84%
“…When an ePTFE membrane implant was scheduled, two intrascleral pockets were dissected with a bevel-up crescent knife, continuing the scleral bed under the flap at its two vertical edges, with an extension of at least 0.5 mm. When MMC use was scheduled, a fluidretaining sponge (such as a Weck-cell sponge), fashioned to be approximately 7 · 3 mm in length and width and about 0.5 mm in depth, was soaked with MMC in a concentration of 0.2 mg ⁄ ml and placed on the scleral bed under the scleral flap, as described in a previous study (Cillino et al 2005). The sponge was left in position for 2 min, with the conjunctival flap pulled over the scleral flap in order to make the Tenon's-capsule side of the conjunctiva get in contact with the MMC.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…32,33 There is also evidence for a similar role of MMC in primary DS. [34][35][36][37][38][39] The decision to use MMC during individual surgical cases was difficult to pinpoint from our database. Patients in the MMC group were slightly younger and probably had worse visual field (VF) mean deviation.…”
Section: Discussionmentioning
confidence: 99%